Catecholamine levels in a Ramadan fasting model in rats: a case control study. Issue 4 (3rd July 2016) - Bucaktepe, Pakize Gamze Erten; Akdağ, Mehmet; Dasdag, Suleyman; Celepkolu, Tahsin; Yılmaz, M. Abdullah; Demir, Vasfiye; Haris, Parvez
ABSTRACT: Eating habits as well as physical exercise are very important for a healthy lifespan. Ramadan-type fasting, which is food and water avoidance during the daylight period for four weeks, has drawn attention due to its positive impacts on metabolism and health. The aim of this study was to compare the blood and urine catecholamine (CA) levels in fasting and non-fasting rats, in terms of stress response. A total of 20 male rats were randomly divided into a fasting group and a control group. Four weeks later, blood and urine samples were taken after decapitation. Analysis of CAs was done using high-performance liquid chromatography with florescence detection (HPLC-FLD). The dopamine (DA), adrenaline (ADR) and noradrenaline (NA) blood and urine concentrations were found to be higher in the fasting group compared to the control group, but the difference was statistically significant only for the blood DA levels ( p < 0.05). In the fasting group, the blood values of ADR and NA correlated with each other but not with the DA levels, whereas there was correlation among the urine levels of DA, ADR and NA. In the control group, the blood and urine values of DA, ADR and NA correlated with each other. The differences observed in the blood and urine CAs indicate a specific regulation of CAs in Ramadan-type fasting, which needs to be investigated thoroughly in future studies.